Germination and seedling growth of indigenous aman rice under salt stress (Journal of the Bangladesh Agricultural University, 2017)
The experiment was conducted at the Agronomy Laboratory of Agrotechnology Discipline, KhulnaUniversity, Khulnato determine the effect of salt stress on germination and seedling growth of indigenous Aman rice varieties during June, 2015 to December, 2015.  The salt tolerant landraces will be used as genetic resource for variety development program in future. The factorial experiment consists of two factors such as ten indigenous Aman rice varieties and four levels of salt solutions viz EC (dS m−1) of 5, 10 and 15 with control (distilled water). The experiment was laid out in Completely Randomized Design (CRD) with three replications. The interaction effects between variety and salinity on germination and seedling growth parameters of indigenous Aman rice varieties were varied significantly. It was found that germination capacity, energy, speed, seedling vigor index, root length and shoot length of rice were decreased gradually with increasing salinity. The germination energy and germination speed of most varieties were drastically reduced at 10 dS m−1 or higher salinity levels. The germination capacity of Hatibazor, Boushohagi, Shadagotal and Moinamoti were recorded 97.66 %, 99.33%, 98.0 % and 97.33%, respectively at 15 dS m−1 water salinity in laboratory condition. The results revealed that the indigenous Aman rice varieties named Boushohagi, Shadagotal, Hatibazor, Moinamoti, Motha were performed better over other varieties considering of germination and seedling growth parameters.J. Bangladesh Agril. Univ. 15(2): 182-187, December 2017